EMERGENCY EFFICIENCY AND PRODUCTIVITY OF DIFFERENT POTATO SEED TYPES - TEIXEIRA, Alexsandro Lara; SILVA, Camila Andrade; PEIXOUTO, Leandro Santos; LEPRE, André Luiz (Scientia Agraria, 2010)
The potato seed in Brazil is marketed by weight and not on the number of tubers, which is a factor that affects on the cost of production, making essential the knowledge of how characters like weight and emergency efficiency of potato seed can influence the performance of culture. The purpose of this study was to identify the size of the potato seed that has greatest emergency and productivity. Five potato seed types (I, II, III, IV e V) were evaluated, according to the classification of the state of Minas Gerais. The experimental design used in the first trial was completely randomized (greenhouse), and in two field trials were used randomized complete block, all with five replications. The results showed that there is difference in most traits, except to average weight of tubers. It was observed that larger potato seed has more number of eyes, shoots and therefore more rods. It was noted that the larger potato seeds provide increases in productivity (t ha-1), whereas the same spacing between plants. Type I potato seed has the higher fresh weight. There are differences in productivity, given the same spacing, for different types of potato seed, and the Type I has the highest tuber production.